Millennial Worker Retention Strategy; A Literature Study - Agus Sudono; Syamsul Hadi Senen; Rofi Rofaida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Millennial workers are known to easily change jobs, tend to be free of expression, and want fast progress in careers and competencies, they dominate with a proportion of 56.1% of the total workforce. This study aims to reveal recommendations for retention strategies for millennial workers from recent studies. The method used is a systematic literature review of journal articles published in reputable international journals from the Emerald and SAGE Journals databases. The search results identified 9 journal articles relevant to the research objectives. The results of the study show that a competitive climate that values achievement, openness to express opinions, open opportunities to pursue careers and competencies, quality mentors, and appreciation for expression creates a culture in relevant corridors are a series of strategies that are seen as able to accommodate millennial workers to develop, last longer, and improve the competitiveness of company.